Superdotação, transtorno de déficit de atenção/hiperatividade e dupla excepcionalidade - Ogeda, Clarissa Maria Marques (Editora UNESP, 2023)
The book presents its readers with new ways to understand the phenomena of Giftedness and Attention Deficit/Hyperactivity Disorder. Through a rigorous methodological design, the author investigates the diagnosis of ADHD in subjects with gifted behavior, as well as Giftedness in subjects with ADHD, and expands discussions on the manifestation of dual exceptionality based on national and international theoretical references. KETILIN MAYRA PEDRO